Gas sensors and factors influencing sensing mechanism with a special focus on MOS sensors - Nadargi, Digambar Y. Y.; Umar, Ahmad; Nadargi, Jyoti D. D.; Lokare, Smita A. A.; Akbar, Sheikh; Mulla, Imtiaz S. S.; Suryavanshi, Sharad S. S.; Bhandari, Nagesh L. L.; Chaskar, Manohar G. G. (Journal of Materials Science, 2023)
Industrialization and its progress are very important for the economy and to move towards prosperity, stimulating innovation and creating jobs. Nonetheless, industrialization has negative impacts, if not done judiciously, such as pollution, increased greenhouse gas emissions, and global warming. Therefore, amenity-with-security is of fundamental significance in a new and dynamic lifestyle. A gas sensor is one of the crucial devices for monitoring and subsequently preserving the clean atmosphere among a number of other safety technologies. In-depth assessments of gas sensors and their necessity in the environment (air) pollution are provided in the current review. With a special emphasis on metal oxide semiconductor (MOS)-based gas sensors, the review includes a thorough study of gas sensors and the factors relating to sensing mechanisms. It not only describes the basic concepts and brief history of gas sensors, but also highlights the schemes responsible for improving the gas sensing properties and state-of-art literature review. These schemes include (1) surface engineering/morphological tuning and (2) bulk and surface doping. To keep scientific rigour and in-depth analyses, this review focuses on these two schemes only. In the doping area, the emphasis is given on graphene loading, decorated with nanoparticles of noble metals, spillover mechanism, and heterojunction (p-n, n-n, and p-p) formation. The conclusion summarizes the most optimized MOS gas sensors with enhanced gas sensing capabilities. The emphasis is given to formulate the article in such a way that it will be useful for the beginners who wish to explore the gas sensor research field, as well as to the established researchers to further improve the sensing capabilities of MOS gas sensors.